Editorial: Navigating Uncertainty Through Policy Transformation - Wijaya, Shadu Satwika; Satyawan, Darmanto Sahat; Gunarto, Guntur; Nuraini, Hikmah (Public Policy and Management Inquiry, 2025)
This editorial explores policy transformation as a strategic framework for navigating the era of structural uncertainty defined by rapid sociopolitical, economic, and technological changes. In Indonesia, this situation is exacerbated by geographical disaster vulnerability and significant challenges to the integrity, neutrality, and professionalism of the State Civil Apparatus (ASN) during political transitions. The sources indicate that rigid, sectoral policy models have proven insufficient to address complex issues such as rural poverty, regional inequality, and the multidimensional pressures of urbanization in cities like Surabaya. Furthermore, the universal application of Western Public Administration (WPA) often lacks cultural legitimacy and fails to address grassroots realities because it neglects Indonesia's unique social and institutional contexts. To bridge the gap between policy design and implementation reality, this editorial proposes a framework of embedded autonomy and collaborative governance where bureaucrats are designed as autonomous actors who are institutionally obligated to network and negotiate with local communities. This approach is exemplified by successful village potential management through Village-Owned Enterprises (BUMDes), which strengthen local economies while building social trust. Ultimately, effective policy transformation requires the restoration of the merit system to protect the bureaucracy from politicization and the development of non-Western paradigms that prioritize microsociety and human capital as the primary drivers of public service innovation